Sorgo sacarino como substrato para a produção de etanol e modelagem da cinética de fermentação - Zanata, Júlio Henrique (Universidade Federal de São Carlos, 2023)
Sorghum is a grass with significant cultivation in several countries and of great agricultural and livestock importance, mainly due to the inclusion of its grain in animal nutrition, being the fifth most produced cereal in the world. A broth rich in fermentable sugars can be obtained from the culms of the saccharin variety of sorghum, which has been the subject of several studies aiming at it as an alternative source to produce fuel alcohol and to reduce the idle period of sugarcane mills in the off-season. Unlike sugarcane, a traditional raw material in Brazil, the cultivation of sorghum is not limited to the tropical climate, it adapts to different types of soil and is better resistant to drought. In the USA, where the production of ethanol from cereals is already well structured, sorghum grains are widely used for this purpose, where they can be processed with corn grains. In the last decade, the first corn ethanol plants appeared in Brazil, opening possibilities for sorghum grain and, consequently, contributing to the decentralization of sugar and alcohol industry. This final paper sought to expose the panorama and perspectives of the industrial production of ethanol from sorghum in Brazil and, with data from fermentative tests in the literature, the mathematical modeling of the concentration profiles of cells, substrate and product was carried out throughout the process, having sweet sorghum grains and juice as sources of sugars. With the support of the Python programming language, mass balances were solved, with cell growth kinetics based on the Monod model. The adjusted parameters generated simulated profiles with good approximation to the experimental data. It was also possible to estimate a total ethanol yield of 6,192 L/ha/harvest, which makes the use of this raw material interesting, considering its other characteristics.
Sugar sorghum as a substrate for ethanol production and modeling of fermentation kinetics
Keywords: Etanol; Sorgo; Fermentação; Cinética; Modelagem; Ethnaol; Sorghum; Fermentation; Kinetic; ENGENHARIAS::ENGENHARIA QUIMICA